7-ethylindole: A new efficient liquid organic hydrogen carrier with fast kinetics. (12th July 2018) - Chen, Zhiwen; Yang, Ming; Zhu, Ting; Zhang, Zhenlin; Chen, Xuedi; Liu, Zhenjie; Dong, Yuan; Cheng, Guoe; Cheng, Hansong
Abstract: We report a discovery of a new member of the liquid organic hydrogen carrier (LOHC) family, 7-ethylindole (7-EID), with a low melting point of −14 °C and a decent hydrogen content of 5.23 wt%. Hydrogenation of the compound was carried out over a commercial 5 wt% Ru/Al2 O3 catalyst in the H2 pressure range of 5–8 MPa and a temperature range of 120–160 °C, respectively. It was found that the hydrogenation rate positively correlates with the reaction temperature. However, the rate was barely effected by the H2 pressure if the pressure exceeds 6 MPa. The estimated apparent activation energy of 7-EID hydrogenation is 51.5 kJ/mol. The fully hydrogenated product, octahydro-7-ethylindole (8H-7-EID), was used as the reactant for the dehydrogenation reaction at 170–200 °C over a 5 wt% Pd/Al2 O3 catalyst. Full dehydrogenation of 8H-7-EID to 7-EID can be achieved within 270 min at 190 °C. The apparent activation energy of 8H-7-EID dehydrogenation was calculated to be 101.9 kJ/mol at 170–200 °C. The liberated H2 was found to be of high purity, which meets the requirement of proton exchange membrane fuel cells. Highlights: 7-ethylindole was reported as a LOHC candidate with hydrogen content of 5.23 wt% and a low melting point of −14 °C. Full hydrogenation of 7-Ethylindole (7-EID) was realized at 130–160 °C with 7.0 MPa H2 pressure. Full dehydrogenation of octahydro-7-ethylindole (8H-7-EID) was realized at 170–200 °C over a 5 wt% Pd/Al2 O3 catalyst. The kinetics of both hydrogenation and dehydrogenation processes were explored in details. The released H2 was detected to be relatively pure and fully satisfies the needs of fuel cells.